Agrobacterium-mediated transformation by using immerse and agroinfiltration method for genome editing of orchids with CRISPR/Cas9 - Subchan, A. N.; Nopitasari, S.; Setiawati, Y.; Zubaidah, L.; Nikmah, N.; Lawrie, M. D.; Sasongko, A .B.; Matsumoto, S.; Yoshioka, Y.; Semiarti, E. (International Society for Horticultural Science, 2022)
CRISPR/Cas9 is an effective molecular tool for genome editing in the horticultural plant for quality improvement. Agrobacterium-mediated transformation is an appropriate method for gene transfer in the genetic transformation in plant. The objective of this study is to determine an effective method of Agrobacterium-mediated transformation in orchids, by using the methods of agroinfiltration. In this study, CRISPR/Cas9 with the VAR2 and PDS3 as target genes for genome editing were used. The methods were as follows: 1) transformation the pRGEB32 containing the T-DNA into A. tumefaciens EHA105; 2) confirmation of the presence of T-DNA in pRGEB32/A. tumefaciens EHA105 with PCR using Cas9 and HPT primers; 3) transfer T-DNA into the plant genome using agroinfiltration and Agrobacterium-mediated by immersion; 4) confirmation of the integration of T-DNA in transformant genome. Transformation using Agrobacterium-mediated through seedling immersion only showed that D. lineale and D. capra were successfully transformed with the value of transformation efficiency was 2.22%, while the transformant candidate was not found in the seedling of D. macrophyllum. In the agroinfiltration method, Agrobacterium carrying T-DNA with the construction of CRISPR/Cas9 was inserted with a needle into the pseudobulb of a one-year-old orchid plantlet. These results were confirmed by positive results of PCR analysis on the genome of Dendrobium macrophyllum amplified with Cas9 (402 bp), HPT (545 bp), VAR2 (723 bp) primers, and ACTIN (114 bp) used as internal control. In contrast, all positive agroinfiltration samples carried T-DNA (100%). From this it can be concluded that the agroinfiltration method has a high potential to be used for gene transfer in orchids.